Neuropsychiatric adverse effects of mefloquine - What do we know and what should we do? - Nosten, F; van Vugt, M (1999)
Malaria is still one of the most important tropical diseases, killing millions every year. The number of effective drugs is limited, because of the ability of the causative parasite Plasmodium falciparum to develop drug resistance. Mefloquine, if possible in combination with an artemisinin derivative, is the only efficacious treatment left for uncomplicated but highly multidrug-resistant P. falciparum infections encountered in some areas. Mefloquine remains effective in most endemic areas worldwide for both prophylaxis and treatment of malaria. Generally, mefloquine is well tolerated but it is associated occasionally with neuropsychiatric adverse effects, whether used as treatment or for prophylaxis. In recent years, mefloquine has acquired a bad reputation mainly because of reports of neuropsychiatric reactions in travellers. These reports were widely publicized and amplified by the media. As a result, the confusion about recommendations for the prophylaxis of malaria has deepened and decisions on prophylactic regimens have been made that could have serious consequences. However, there is little evidence that the use of mefloquine should be avoided because of the risk of these adverse effects. Although studies have shown that mefloquine is associated with neuropsychiatric adverse effects, most of these events have been mild and self-limiting. Some predisposing factors to the occurrence of neuropsychiatric adverse effects, such as a family history or a past history of neuropsychiatric disorders, recent (last 2 months) previous exposure to mefloquine or use of psychotropic drugs, were identified. Use of mefloquine should not be considered in these cases. Updated information about contraindications to mefloquine and the risk of malaria in areas visited should be available for medical professionals and patients. All antimalarials have adverse effects; it is therefore essential to balance the risks and the benefits each time a malaria prophylaxis regimen is prescribed.